Code name: Pale Horse : how I went undercover to expose America's Nazis - Payne, Scott (FBI agent); Shephard, Michelle (Atria Books, 2025)
"For readers of The MAGA Diaries and Hate in the Homeland, an eye-opening and crucial true story of one man risking his life to infiltrate the most dangerous neo-Nazi group in the United States. When Scott Payne was growing up, he never envisioned a future that included what happened on Halloween night 2019. Out in the woods of Georgia, he tried desperately to save a goat from being sacrificed in a ritual by a group of neo-Nazis without revealing that he was actually an undercover agent. Now, this retired FBI agent reveals how and why he infiltrated the rapidly growing American Nazi group, The Base. Known as the "Hillbilly Donnie Brasco," Payne was guided through some of the most terrifying and risky assignments in the FBI's history by his devotion to his family and his Christian faith. Timely and unputdownable, Code Name: Pale Horse is an unflinching look at one of biggest threats in national security, as well as an inspiring memoir from an American hero"--